Planejamento estratégico da Receita Federal do Brasil: análise comparada com órgãos similares de outros países - Almeida, Antonio Carlos de (2017)
Strategic planning is a fundamental tool in the management of organizations. The public administration has evolved in this sense and adopts practices developed for organizations in general, with the appropriate adjustments. In order to answer the expectation of understanding the strategic planning of the Brazilian tax administration, this paper has the objective of describing and comparing the strategic planning of the Federal Revenue of Brazil with similar institutions of other countries. The tax administration is a highly relevant part in the context of the public administration of all nations, an essential part of the organization and functioning of states and their public policies. Although limited by the availability of information, the proposed comparative analysis has the power to provide a broad view of the respective realities in this sector and the respective strategic initiatives that have guided them. From a qualitative approach, it is an exploratory and descriptive study, characterizing itself as a comparative case study. The results show that strategic planning is an important element of the organizational learning process. They also show that the Brazilian tax administration adopts a strategic plan according to international standards and that the tax administrations analyzed have similarities, generally having a strategic orientation aimed at obtaining resources for the maintenance of the State and its public policies, for the preservation of the base tax incentives for voluntary compliance with obligations, innovative technological solutions and the search for recognition and respectability. It was also observed that in the tax administrations of developed countries the vision of the future is aligned with the preservation of society's trust in such organizations, as a result of a consolidated tax system and also in the valuation of people.